2004
DOI: 10.1523/jneurosci.5407-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Protein Kinase Activation Is Required for Metabotropic Glutamate Receptor-Dependent Long-Term Depression in Hippocampal Area CA1

Abstract: Activation of group 1 metabotropic glutamate receptors (mGluRs) induces long-term depression (LTD) of synaptic transmission that relies on dendritic protein synthesis. We investigated the signal transduction pathways required for mGluR-LTD to identify candidate mechanisms for mGluR regulation of synaptic protein synthesis. Our results demonstrate a role for extracellular signal-regulated protein kinase (ERK), a subclass of the mitogen-activated protein kinases (MAPKs), in mGluR-LTD in area CA1 of the rat hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
232
2
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(258 citation statements)
references
References 42 publications
22
232
2
2
Order By: Relevance
“…Although it has been previously shown that ERK phosphorylation is required for both LTP [9,10] and LTD [26,11] in hippocampal CA1 as well as LTD in the cerebellum [8] and LTP in other cortical areas [12] , we provide the first evidence that ERK activation is required for striatal LTD induction.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Although it has been previously shown that ERK phosphorylation is required for both LTP [9,10] and LTD [26,11] in hippocampal CA1 as well as LTD in the cerebellum [8] and LTP in other cortical areas [12] , we provide the first evidence that ERK activation is required for striatal LTD induction.…”
Section: Discussionmentioning
confidence: 45%
“…For example, stimuli inducing LTP in area CA1 of the hippocampus potently activate ERK [8] , whereas pharmacological inhibition of MEK, an upstream activator of ERK, inhibits LTP [8,9] . The participation of ERK in synaptic plasticity has also been found in other brain regions [10,11,12] (eg, LTD in the cerebellum and LTP in the visual cortex).…”
Section: Introductionmentioning
confidence: 82%
“…By contrast, however, an ERK-dependent cascade is implicated in leptin-induced LTD, as selective inhibitors of ERK activation block leptin action at P5-8 [29]. The role of ERK in leptin-induced LTD displays similarities to mGluR-dependent LTD, as activation of ERK is necessary for endocytosis of AMPA receptors and LTD [51]. Thus, although AMPA receptor internalization may be common to both leptin-induced LTD at P5-8 and LFS-induced LTD, it is likely that divergent signalling pathways promote AMPA receptor removal from synapses.…”
Section: Leptin-driven Changes In Synaptic Efficacy Display Parallelsmentioning
confidence: 99%
“…The ERK 1/2 MAPK pathway is also required for metabotropic glutamate receptor-dependent long-term depression (Gallagher et al, 2004). We tested whether ERK 1/2 MAPK also played a role in adenosine-mediated synaptic depression.…”
Section: Adenosine-induced Depression Of Synaptic Transmission Is Medmentioning
confidence: 99%